2017
DOI: 10.3201/eid2304.161549
|View full text |Cite
|
Sign up to set email alerts
|

Zika Virus Seroprevalence, French Polynesia, 2014–2015

Abstract: During 2013–2014, French Polynesia experienced an outbreak of Zika virus infection. Serosurveys conducted at the end of the outbreak and 18 months later showed lower than expected disease prevalence rates (49%) and asymptomatic:symptomatic case ratios (1:1) in the general population but significantly different prevalence rates (66%) and asymptomatic:symptomatic ratios (1:2) in schoolchildren.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
140
7
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 161 publications
(163 citation statements)
references
References 14 publications
13
140
7
2
Order By: Relevance
“…Given the small numbers, a statistically significant link between congenital WNV infection and microcephaly was not established. It is worth noting that the association of WNV infection with congenital malformation in this study resembles that observed from a larger retrospective analysis of ZIKV-induced congenital diseases during the 2013 outbreak in French Polynesia where there were 95 cases of microcephaly in 10,000 pregnancies (rate of 0.95%) and the seroprevalence was 50% ( 46, 47 ). Thus, it is possible that the rate of flavivirus-induced congenital malformations could be similar for WNV and ZIKV, but the overall impact of congenital ZIKV infection is much greater because of the comparatively low seroprevalence rate of 1–5% for WNV ( 48, 49 ).…”
Section: Discussionsupporting
confidence: 80%
“…Given the small numbers, a statistically significant link between congenital WNV infection and microcephaly was not established. It is worth noting that the association of WNV infection with congenital malformation in this study resembles that observed from a larger retrospective analysis of ZIKV-induced congenital diseases during the 2013 outbreak in French Polynesia where there were 95 cases of microcephaly in 10,000 pregnancies (rate of 0.95%) and the seroprevalence was 50% ( 46, 47 ). Thus, it is possible that the rate of flavivirus-induced congenital malformations could be similar for WNV and ZIKV, but the overall impact of congenital ZIKV infection is much greater because of the comparatively low seroprevalence rate of 1–5% for WNV ( 48, 49 ).…”
Section: Discussionsupporting
confidence: 80%
“…However, the demonstration of nonvector‐borne transmission through sexual contact and the transfusion of contaminated blood products has raised concerns over the safety of the blood supply in areas with epidemic and endemic ZIKV . When comparing ZIKV with other arboviruses (Table ), infection results in a high percentage of asymptomatic viremic carriers, similar to DENV and WNV but unlike chikungunya virus (CHIKV). Notably, ZIKV, like WNV, causes various neurologic symptoms.…”
Section: Comparison Of Properties and Characteristics For Prominent Ementioning
confidence: 99%
“…La seroprevalencia estimada al final de la epidemia era del 49%, pero fue del 66% en los escolares de Tahití. Numerosos casos eran asintomáticos [66] . En esta ocasión, la incidencia del síndrome de Guillain-Barré se multiplicó por 17 con respecto a su incidencia habitual.…”
Section: Infección Por El Virus De Zikaunclassified